Contemporary society and neoliberalism - Olimpo Suárez, José (Estudios de Filosofía, 1993)
Theoretical discussion on reactions between the neoliberal conception and philosophy have hardly attracted attention in contemporary society. Interest has centered mainly on socio-economic aspects. A brief statement is made of three conceptual domains participating in the discussion: economics, politics and theology. The authors considered are Adam Smith, John Rawls and Michel Novack.